Clinical Characteristics of Snakebite Envenomings in Taiwan - Yan-Chiao Mao; Po-Yu Liu; Kuo-Lung Lai; Yi Luo; Kuang-Ting Chen; Chih-Sheng Lai (Toxins)
Snakebite envenomings continue to represent a major public health concern in Taiwan because of the presence of various venomous snakes whose habitats intersect with human activities. This review provides a comprehensive analysis of the clinical characteristics, complications, and management strategies associated with snakebite envenomings in Taiwan. Taiwan is inhabited by six principal venomous snakes: Trimeresurus stejnegeri stejnegeri, Protobothrops mucrosquamatus, Deinagkistrodon acutus, Daboia siamensis, Naja atra, and Bungarus multicinctus, each presenting distinct clinical challenges. The clinical manifestations vary from local symptoms such as pain, swelling, and necrosis to systemic complications including neurotoxicity, coagulopathy, and organ failure, depending on the species. Notable complications arising from these snakebite envenomings include necrotizing soft tissue infection, compartment syndrome, respiratory failure, and acute kidney injury, often necessitating intensive medical interventions. This review highlights the critical importance of early diagnosis, the prompt administration of antivenoms, and multidisciplinary care to improve patient outcomes and reduce healthcare costs. Future research is encouraged to enhance treatment efficacy, improve public awareness, and develop targeted prevention strategies. By identifying gaps in current knowledge and practice, this work contributes to the global literature on envenoming management and serves as a foundation for advancing clinical protocols and reducing snakebite-related morbidity and mortality in Taiwan.